'Des fils invisibles nous relient': Comparative memory in Caribbean life-writing. Issue 1 (July 2016) - Cooper, Sara-Louise
Abstract : This article contributes to debates on comparative approaches to the memory of the Holocaust and Atlantic slavery. It examines comparisons between colonial and Second World War histories in the récits d'enfance by three French-speaking Caribbean writers, Patrick Chamoiseau, Gisèle Pineau and Maryse Condé. It argues that because there are significant difficulties involved in approaching the Caribbean's colonial history directly, these authors approach it obliquely through the more recent history of the Second World War. The comparative approaches of these literary texts anticipate events in the public sphere such as the 2001 recognition by the French government of slavery as a crime against humanity or Nicolas Sarkozy's failed 2008 proposal that every French school child should be assigned one of the child victims of the Holocaust to remember. Attention to these comparative approaches is valuable because it points to connections between literature, collective memory and public policy and brings to light the multiple, intersecting histories at play in the French-speaking world. The article concludes by examining the ways in which literary language allows these authors to foreground the linguistic and imaginative processes which create links between separate historical events while maintaining a sense of their difference.